Cartilaginous markers expression in human articular chondrocytes overexpressed with SOX9 gene - Mohamad Sukri, Norhamiza; Mat Jusoh, Nurul Syamimi; Mohadis, Hanisah Mohd; Md Nazir, Noorhidayah; Abdul Rahman, Rozlin; Ahmad Radzi, Muhammad Aa'zamuddin; Zulkifly, Ahmad Hafiz; Hashi, Abdurezak Abdulahi; Mohammad, Mohd Yusof; Sha'ban, Munirah (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2014)
SOX9 is an essential transcription factor for chondrocyte differentiation and cartilage formation. The limited regenerative capacity of cartilage has led to the development of various treatment modality including gene transfer approaches. In this study, we transiently overexpressed or transfected SOX9 gene in articular chondrocytes derived from consented patients after joint surgery. The aim was to achieve optimum transfection effect by optimizing the lipofection procedure using various DNA concentrations. Chondrocytes were overexpressed with 2.0μg, 4.0μg and 6.0μg of pcDNA3-SOX9. The transfection effect on chondrocytes was assessed through the expression of collagen type II, aggrecan, SOX9 and collagen type I using the two-step reverse-transcriptase polymerase chain reaction (RT-PCR). Results showed that at low DNA concentration, the SOX9 transfection up-regulates all cartilage-specific markers expression, but down-regulates collagen type I. Hence, optimum transfection effect can be achieved using low DNA concentration. The ability to sustain the cartilage-specific markers indicates potential implications in cartilage engineering.